1997
DOI: 10.1038/sj.leu.2400773
|View full text |Cite
|
Sign up to set email alerts
|

Sequential analysis of bone marrow and peripheral blood after stem cell transplant for myeloma shows disparate tumor involvement

Abstract: Treatment with combination chemotherapy has not resulted in that PB stem cell harvests are often contaminated with myelong-term remissions in multiple myeloma (MM) despite loma tumor cells. 5,[8][9][10][11] In fact, one study indicated that the advances in drug discovery and protocol improvement over the presence of contaminating tumor cells in the autograft was 10,[18][19][20] We have previously shown that although the BM tumor burden is significantly depleted following high-dose Introduction chemotherapy, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 2 publications
1
17
2
Order By: Relevance
“…The failure of a second cycle of HDT to further reduce the numbers of clonotypic cells in PB indicates that there is a compartment of circulating cells belonging to the myeloma clone that is resistant even to sequential high-dose melphalan. These data do not match those published by Billadeau et al, 17 who reported fairly stable levels of circulating clonotypic cells in the course of a single cycle of HDT. Previous studies from our group had revealed that, indeed, circulating CD19-positive clonotypic cells did not decline in comparison to the corresponding numbers prior to HDT, while CD19-negative clonotypic cells were reduced significantly.…”
Section: Discussioncontrasting
confidence: 56%
“…The failure of a second cycle of HDT to further reduce the numbers of clonotypic cells in PB indicates that there is a compartment of circulating cells belonging to the myeloma clone that is resistant even to sequential high-dose melphalan. These data do not match those published by Billadeau et al, 17 who reported fairly stable levels of circulating clonotypic cells in the course of a single cycle of HDT. Previous studies from our group had revealed that, indeed, circulating CD19-positive clonotypic cells did not decline in comparison to the corresponding numbers prior to HDT, while CD19-negative clonotypic cells were reduced significantly.…”
Section: Discussioncontrasting
confidence: 56%
“…To date, studies focusing on a continuous determination of the tumor load up to the development of PD are limited. The study of Billadeau et al 11 described that the PB tumor burden remains rather constant in six MM patients prior to and post transplantation with only one sample analyzed at the time of PD. In line with Billadeau's results, Rasmussen et al 12 reported a reduction of clonal cells in PB after induction therapy with no further changes in the course of the HDT in seven MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study was performed in order to quantitate the amounts of circulating clonotypic CD19 ϩ and CD19 Ϫ cells prior to and post-HDT with PBSCT and to consider both flow cytometry and molecular techniques as a measure of the tumor cell content in PB of patients with MM. A sequential analysis of whole PB mononuclear cell samples before and after PBSCT was performed by Billadeau et al 12 who showed that the tumor content in PB was independent of the disease stage, and that in most patients the number of malignant cells in PB was only minimally altered by intensive therapy including HDT with PBSCT. Using ASO PCR assays they determined tumor cell proportions ranging from below the detection level to 1.35%.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, Billadeau et al 12 reported that the number of malignant cells in PB remains fairly stable during the course of high-dose treatment. We addressed the question of fate of tumor cells in the CD19 ϩ B cell compartment during high-dose treatment by comparing tumor cell numbers in samples from patients after conventional chemotherapy with those after HDT.…”
mentioning
confidence: 99%